Pattern and frequency of pediatric congenital heart disease at the Cardiac Research Institute of Kabul Medical University, Afghanistan - Abdul Muhib Sharifi (Paediatrica Indonesiana, 2018)
Background Congenital heart disease (CHD) is the most common birth defect, with incidence of 0.7-0.9 live birth; it increases to 2-6% if first degree relative is affected. In Afghanistan majority of births take place at home and routine screening of neonates is not common, so true birth prevalence of CHD cannot be possibly calculated. Therefore, true prevalence of CHD in our population is unknown. Objective To verify the current pattern and frequency distribution of congenital heart disease (CHD) at the Cardiac Research Institute of Kabul Medical University. Methods This retrospective study was conducted in children aged 0-14 years, who underwent echocardiography for possible congenital heart disease from January 2015 to December 2016. Results Of 560 patients who underwent echocardiography, 392(70%) had cardiac lesions. Congenital cardiac lesions were found in 235 (60% of those with lesions) patients, while 157 (40%) patients had rheumatic heart disease. Patients with CHD were further subdivided into acyanotic and cyanotic groups. The majority of acyanotic group had isolated atrial septal defect (55%) while the most common lesion in the cyanotic group was Tetralogy of Fallot (42%). Conclusion Congenital heart defects are the most common heart disease in the pediatric population presenting at the Cardiac Research Institute of Kabul Medical University. Atrial septal defect (ASD) was the most common acyanotic defect, while Tetralogy of Fallot (ToF) is the most common cyanotic defect.